PENGARUH MITOS PADA PEMBELIAN SUSU BEAR BRAND SEBAGAI PENANGKAL VIRUS CORONA: STUDI KASUS KONSUMEN SUSU BEAR BRAND - Reni Kurnia Ferdiana; Ginanjar Rahmawan (Globalwriting Academica Consulting & Publishing, 2022)
This study aims to determine whether there is a significant effect of myth, panic buying, brand image, and perception variables on purchasing decisions for Bear Brand milk during the corona virus. The type of method used in this study is a quantitative method with a non-probability sampling sample collection technique, namely the accidental sampling technique of 100 respondents through questionnaires. Researchers processed the data from the questionnaire using the SPSS version 16 software program. The results of this study prove that there is a positive and significant effect of independent variables (myths, panic buying, brand image, and perception) on the decision to purchase Bear Brand milk during the Corona virus.